Pengaruh Konsep Vernakular Jaga Satru Terhadap Ruang Kawasan Permukiman di Desa Adat Tenganan Pegeringsingan - I Made Oka Handara made; Dwita Hadi Rahmi dwita (Publikasi Indonesia, 2022)
Tenganan Pegeringsingan Traditional Village is part or belongs to three Bali Aga Villages located in the province of Bali. The values and traditions of their ancestors are strongly maintained by the residents of the Tenganan Pegeringsingan Traditional Village. The location of this village is in Manggis District, Karangasem Regency. Tenganan Pegeringsingan Traditional Village has the concept of Jaga Satru or a vernacular concept that only exists in Tenganan Village, that concept is a concept passed down from generation to generation by the local community which was obtained from Dewa Indra as the highest God who is highly trusted by the people of Tenganan Village. The concept of Jaga Satru is the concept of the form of a residential area shaped like a defense